Variability of Soil Physical Properties in a Clay-Loam Soil and Its Implication on Soil Management Practices. (23rd December 2013) - Haruna, Samuel I.; Nkongolo, Nsalambi V.
Abstract : We assessed the spatial variability of soil physical properties in a clay-loam soil cropped to corn and soybean. The study was conducted at Lincoln University in Jefferson City, Missouri. Soil samples were taken at four depths: 0–10 cm, 10–20, 20–40, and 40–60 cm and were oven dried at 105°C for 72 hours. Bulk density (BDY), volumetric (VWC) and gravimetric (GWC) water contents, volumetric air content (VAC), total pore space (TPS), air-filled (AFPS) and water-filled (WFPS) pore space, the relative gas diffusion coefficient (DIFF), and the pore tortuosity factor (TORT) were calculated. Results showed that, in comparison to depth 1, means for AFPS, Diff, TPS, and VAC decreased in Depth 2. Opposingly, BDY, Tort, VWC, and WFPS increased in depth 2. Semivariogram analysis showed that GWC, VWC, BDY, and TPS in depth 2 fitted to an exponential variogram model. The range of spatial variability (A 0 ) for BDY, TPS, VAC, WFPS, AFPS, DIFF, and TORT was the same (25.77 m) in depths 1 and 4, suggesting that these soil properties can be sampled together at the same distance. The analysis also showed the presence of a strong (≤25%) to weak (>75%) spatial dependence for soil physical properties.